The rare and enigmatic mayfly Prosopistoma pennigerum (Müller, 1785): Habitat characteristics, recent records from the Volga (Russia) and Vjosa (Albania) rivers, and a proposal for flagship species status. Issue 12 (16th November 2021) - Schletterer, Martin; Weiss, Steven J.; Kuzovlev, Vyacheslav V.; Vitecek, Simon; Borgwardt, Florian; Graf, Wolfram
Abstract: Nymphs of all 29 described Prosopistoma species share a conspicuous synapomorphy: a round mesonotal shield, the carapace. They occur in the Palaearctic (nine species), the Oriental (12 species) and the Afrotropic as well as Australian regions (six and two species, respectively). Relatively little is known about their ecology, but past and extant distribution patterns indicate an association with undisturbed conditions. Prosopistoma pennigerum is a rare European mayfly with conspicuous nymphs. Formerly common in large rivers, it has been extirpated from central Europe over the last century. This study evaluated general habitat characteristics and human pressures for historical and current records of this rare species. Prosopistoma pennigerum is currently known from only three European rivers, all with gravel substrates, naturally dynamic discharge regimes, summer‐warm water temperatures, and little human pressure. This study showed that nymphs from the Vjosa and upper Volga rivers, two relatively natural watercourses 2, 000 km apart, are morphologically indistinguishable, and show no variation across a ca. 600‐bp fragment of the mitochondrial cytochrome c oxidase I gene. Flagship species were first designated in the 1980s, when charismatic species with high habitat requirements such as the Bengal tiger or the giant panda, but also invertebrates are used to communicate conservation and protection needs. We propose that Europe's rarest mayfly P. pennigerum, with its unusual nymphs and remaining populations in naturally dynamic river courses, can serve as a flagship species promoting the preservation of ecological integrity in European rivers.